PENGARUH PERPUTARAN PERSEDIAAN DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA TOKO-TOKO DI SEKITAR PASAR HORAS PEMATANG SIANTAR - Danri Siboro; Victor H Sianipar; Dame Ria Rananta Saragi (POLITEKNIK LP3I JAKARTA, 2022)
Shops are essential because they can create business fields to support daily economic needs. Inventory Turnover is a crucial thing in trading business operations. This study aims to determine whether inventory turnover and sales growth affect the profitability of shops around the Horas Market Pematang Siantar. This study uses primary data. Questionnaires were distributed to business actors around the Horas Market Pematangsiantar. The respondents in this study amounted to 32 stores. This study used a quantitative approach and processed data from questionnaires transformed through a Likert scale. At the same time, the analysis used in this study is a simple linear regression with a significant level of 5%. There is a positive influence between inventory and sales at shops around the Horas Market Pematangsiantar, where the t.count value is 2.672 > table is 1.69389—evidenced by the coefficient of determination R Square of 19.2%. In addition, there is a positive influence between inventory and profitability in shops around the Horas Market Pematangsiantar, where the t.count value is 2.245 > table is 1.69389. Evidenced by the coefficient of determination R Square of 14.4%.Key word: Inventory, Sales Growth, And Profitability